An Analysis of Power Exercise in H. G. Wells’ The War of the Worlds - Rifki Zamzam Mustaffa (Passage, 2017)
The novel entitled The War of the Worlds has several issues which is interesting to be studied. One of them is the issue of power which becomes the main focus of the present study. Since the novel portrays the war between humans and aliens (specifically, the Martians’ invasion of the Earthlings) and arguments among humans (the Earthlings) illustrate the exercise of power, the bases of power proposed by Raven (2008) are applied in this study to examine the power-related phenomena. Furthermore, the power exercise is analyzed by focusing on conflicts among characters, particularly the conflicts between the Martians and the Earthlings as well as the conflicts among the Earthlings. The findings of the study discovered that the distinctive way of exercising power, particularly in the conflicts, is through coercion and information. This shows that the way power is exercised in the novel is comprehended to be the way text shows its bias towards logical and empirical way of thinking. Keywords: power exercise, conflicts, coercion, information, textual power